Outcomes of Pressure‐Induced Cranial Neuropathies from Allergic Fungal Rhinosinusitis. (12th January 2015) - Illing, Elisa A.; Dunlap, Quinn; Woodworth, Bradford A.
Abstract : Objectives: Allergic fungal rhinosinusitis (AFRS) may present with significant bone erosion of the orbital walls or cranial base. Although proptosis is fairly common, cranial neuropathies are rarely reported. The objectives of this study are to describe strategies for AFRS‐induced neuropathies and evaluate ophthalmologic outcomes following endoscopic sinus surgery. Study Design: Case series with chart review. Setting: Tertiary referral center. Subject and Methods: A retrospective review identified 9 patients treated from 2008 to 2014 with AFRS‐induced cranial neuropathies. Data regarding patient demographics, preoperative imaging, ophthalmologic symptoms, surgical intervention, histopathologic findings, and postoperative sinonasal and ophthalmologic outcomes were recorded. Results: Patients with AFRS (average age, 38 years) presented with optic neuropathy or abducens nerve palsy. Clinical presentation included unilateral visual loss secondary to optic nerve compression (n = 5), diplopia from unilateral (n = 2) or bilateral (n = 1) abducens nerve palsy, and bitemporal hemianopsia secondary to optic chiasm compression (n = 1). On average, the duration of ocular symptoms was 17 days. All patients underwent endoscopic surgical decompression of the sinuses and oral steroid therapy. Two individuals had an additional optic nerve decompression at the time of surgery. Seven patients had complete return of nerve function, whereas 2 had partial recovery at an average of 5 weeks following surgery. Conclusion: Bone erosion of the sphenoid sinus walls by AFRS can lead to compression of surrounding neural structures producing cranial neuropathies. Identification of these symptoms and prompt surgical decompression and removal of disease, along with aggressive medical therapy, provided excellent outcomes in the current series of patients.